Tocilizumab Initiation based on Indicator in Patients Infected by Coronavirus-19 to Prevent Intubation - Permana, Septian Adi; Sugiarto, Adhrie; Manggala, Sidharta Kusuma; Thamrin, Muhammad Husni; Purwoko, Purwoko; Ganitafuri, Handayu (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has created severe medical and economic consequences worldwide since 2019. Tocilizumab is one of the therapies considered capable of improving the condition of patients with COVID-19. However, there is not much information about the best time to give tocilizumab. METHODS: This was an analytical study with a retrospective cohort design, using the data of 125 patients infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with signs of acute respiratory distress syndrome in Dr. Moewardi Hospital, Surakarta, from March to August 2020. We analyzed various available clinical data to see which factors into clinical improvement with tocilizumab therapy. RESULTS: Most patients showed clinical improvement after administration of tocilizumab. During the follow-up period, 21 patients died despite tocilizumab therapy. Significant risk factors associated with the need for intubation were heart rate, neutrophil, lymphocyte, pH, PaCO2, and PO2. The most influential variable on the need for intubation without being associated with other risk factors was PaO2 (p = 0.003, Confidence Intervals 95%). CONCLUSIONS: Tocilizumab has a role in treating patients infected by SARS-CoV-2, preventing the need for intubation when given to patients in good saturation condition with oxygen supplementation without positive pressure (PaO2 >65mmHg; SpO2 >93%).